Conventional versus biological therapy for prevention of postoperative endoscopic recurrence in patients with Crohn's disease: an international, multicenter, and observational study - Kotze, Paulo Gustavo; Spinelli, Antonino; da Silva, Rodolff Nunes; de Barcelos, Ivan Folchini; Teixeira, Fábio Vieira; Saad-Hossne, Rogério [UNESP]; de Albuquerque, Idblan Carvalho; Olandoski, Marcia; da Silva Kotze, Lorete Maria; Suzuki, Yasuo; Yamada, Akihiro; Takeuchi, Ken; et al. (Intestinal Research, 2015)
Postoperative endoscopic recurrence (PER) occurs in nearly 80% of patients 1 year after ileocecal resection in patients with Crohn's disease (CD). Biological agents were more effective in reducing the rates of PER in comparison with conventional therapy, in prospective trials. The aim of this study was to compare the PER rates of biological versus conventional therapy after ileocecal resections in patients with CD in real-world practice. The MULTIPER (Multicenter International Postoperative Endoscopic Recurrence) database is a retrospective analysis of PER rates in CD patients after ileocecal resection, from 7 referral centers in 3 different countries. All consecutive patients who underwent ileocecal resections between 2008 and 2012 and in whom colonoscopies had been performed up to 12 months after surgery, were included. Recurrence was defined as Rutgeerts' score ≥i2. The patients were allocated to either biological or conventional therapy after surgery, and PER rates were compared between the groups. Initially, 231 patients were evaluated, and 63 were excluded. Of the 168 patients in the database, 96 received anti-tumor necrosis factor agents and 72 were treated with conventional therapy after resection. The groups were comparable regarding age, gender, and perianal disease. There was longer disease duration, more previous resections, and more open surgical procedures in patients on biologicals postoperatively. PER was identified in 25/96 (26%) patients on biological therapy and in 24/72 (33.3%) patients on conventional therapy (P=0.310). In this retrospective observational analysis from an international database, no difference was observed between biological and conventional therapy in preventing PER after ileocecal resections in CD patients.
Keywords: Crohn disease; Recurrence; Tumor necrosis factor-alpha